2016
DOI: 10.1371/journal.ppat.1005901
|View full text |Cite
|
Sign up to set email alerts
|

An RNAi-Based Control of Fusarium graminearum Infections Through Spraying of Long dsRNAs Involves a Plant Passage and Is Controlled by the Fungal Silencing Machinery

Abstract: Meeting the increasing food and energy demands of a growing population will require the development of ground-breaking strategies that promote sustainable plant production. Host-induced gene silencing has shown great potential for controlling pest and diseases in crop plants. However, while delivery of inhibitory noncoding double-stranded (ds)RNA by transgenic expression is a promising concept, it requires the generation of transgenic crop plants which may cause substantial delay for application strategies dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
594
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 444 publications
(627 citation statements)
references
References 47 publications
21
594
0
12
Order By: Relevance
“…Therefore, following the gene silencing treatment, plants turned to be perfectly resistant to the fungal infection. Recently, it was also demonstrated that this gene silencing procedure can also be successful by spraying plant leaves with doublestranded RNAs against fungal (Koch et al, 2016) and viral (Mitter et al 2017) pathogens. It is important to note that application of this technique allows the modification of plant traits without altering the plant's DNA.…”
Section: Golden Rice: Future Prospectsmentioning
confidence: 99%
“…Therefore, following the gene silencing treatment, plants turned to be perfectly resistant to the fungal infection. Recently, it was also demonstrated that this gene silencing procedure can also be successful by spraying plant leaves with doublestranded RNAs against fungal (Koch et al, 2016) and viral (Mitter et al 2017) pathogens. It is important to note that application of this technique allows the modification of plant traits without altering the plant's DNA.…”
Section: Golden Rice: Future Prospectsmentioning
confidence: 99%
“…This knowledge raises the possibility that plants can be protected from pathogens/pests by exogenously supplied RNA Koch et al 2016). Possible agronomic application of environmental RNA is affirmed by the high sensitivity of Fusarium graminearum (Fg) to dsRNAs and siRNAs (Koch et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge raises the possibility that plants can be protected from pathogens/pests by exogenously supplied RNA Koch et al 2016). Possible agronomic application of environmental RNA is affirmed by the high sensitivity of Fusarium graminearum (Fg) to dsRNAs and siRNAs (Koch et al 2016). In support of this notion, spraying a 791 nt long noncoding dsRNA (CYP3RNA), which targets the three Cytochrome P450 lanosterol C-14α-demethylase (CYP51) genes FgCYP51A, FgCYP51B and FgCYP51C of Fg strongly inhibited fungal growth on barley leaves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations